Evaluasi Efektivitas Sistem Tosnus dalam Meningkatkan Digitalisasi dan Efesiensi Pengelolaan Bongkar Muat Petikemas Pada PT Prima Multi Terminal - Suci Ramadhani; Muhammad Irwan Padli Nasution (Universitas 45 Surabaya, 2025)
This study aims to evaluate the effectiveness of the Tosnus System in enhancing digitalization and improving the efficiency of container loading and unloading operations at PT Prima Multi Terminal by utilizing secondary data from previous journal studies, industry reports, and information from news websites and official company publications. A descriptive qualitative approach is used to analyze how the implementation of Tosnus contributes to accelerating information flow, reducing manual processes, and increasing operational accuracy. The findings indicate that the Tosnus System significantly improves coordination between operational units through integrated digital information, resulting in more structured, transparent, and easily monitored container handling activities. Secondary data also shows a reduction in vessel waiting time and improved equipment efficiency supported by real-time monitoring features provided by the system. However, several challenges remain, including dependence on digital infrastructure stability and the need for continuous system updates to maintain optimal performance. Overall, Tosnus demonstrates a positive contribution to advancing port digitalization and enhancing the operational efficiency of PT Prima Multi Terminal